E-LEARNING SEBAGAI MEDIA IMPLEMENTASI PENDIDIKAN KARAKTER BAGI PESERTA DIDIK - Ardian Arief; Pramudya Cahyandaru (Taman Cendekia: Jurnal Pendidikan Ke-SD-an, 2018)
Internet-based learning or e-learning is one of today's learning, along with technological advances; e-learning is increasingly easy to be applied in the learning process. Teachers or lecturers can use it to support the learning process; in addition, learners also find it easy to access the learning. E-learning can be used as a way of character education implementation. It is because basically the concept of e-learning can build the character of each learner through the features or characteristics of e-learning. Some of the characteristics that are built from the application of e-learning characteristic are responsibility, discipline, self reliance, communicative, peace-loving, honest, democratic, and loving achievement.